Preferential solvation of naproxen and piroxicam in ethanol+ water mixtures (2023)
The preferential solvation parameters of naproxen (NAP) and piroxicam (PIR) in ethanol (EtOH) + water binary mixtures were obtained from their thermodynamic properties